Estudo do avanço da frente de carbonatação em compósitos cimentícios produzidos com baixos teores de aditivos incorporadores de ar - Priscilla Coelho Cordeiro (2018)
The use of air entraining admixtures in the production of cementitious matrix composites usually occurs with the purpose of improving their performance when subjected to freeze-thaw cycles, as well as being able to increase its fluidity and workability in the fresh state, allowing the reduction of the amount of water used in the mix. However, the air entraining may also be capable of reducing the absorption of liquids by capillarity in the material and of diminishing the connectivity of its void structure, producing a reduction of the diffusibility of fluids, thus being possible to be used without compromising the service life of reinforced concrete structures. The present study sought to evaluate the effect of the use in low dosage of air entraining admixtures in the advance of the carbonation front, since the speed with which this phenomenon occurs is conditioned to factors that are directly related to its composition, the exposure conditions and the characteristics of its microstructure. In this context, the advance of the carbonation front and the hydrogenation potential (pH) of cylindrical test specimens (CPs) of mortar with a standard dimension of (5 x 10) cm, measured with three different types of air entraining admixtures, maintaining for all mixes the same index of normal consistency according to the procedure specified in NBR 7215: 1996. The reference mix, without additives, was elaborated based on the recommendations of this same standard, adopting a water / cement ratio of 0,48. Measurement of air content in fresh mortar was performed for all mixes. Electrospray ionization mass spectrometry (ESI-MS) indicated that the three admixtures used are sodium lauryl ether sulfate. Characterization tests of the compressive strength of the studied mixes were performed at the ages of 3, 7 and 28 days. The test specimens, submitted to the accelerated carbonation test at 14, 28, 42, 56, 70, 98 and 126 days, were packed in a carbonation chamber, taking as reference the normative standards established in ISO 1920-12:2015 , parallel to the measurement of the pH variation on the surface of the cementitious composite, using specific equipment for this purpose. It was also possible to monitor the pH variation of CPs throughout the ages. The results obtained showed a small reduction in the compressive strength in the mixes in which the air entraining admixtures were used, and an equivalence in the rate of advance of the carbonation front in relation to the reference mix for one of the admixtures used after exposure in chamber. The mixes with two admixtures presented a lower rate of carbonation than the reference mix, but until the 98 days of accelerated tests the four mixes studied were considered statistically equal. After 126 days of exposure in the chamber, Scanning Electron Microscopy (SEM) and Computerized Microtomography (Micro-CT) were performed. The results indicate that the reference mix presented a higher porosity (%) and a larger average pore diameter in relation to the traces with air incorporating additive.